Analysis of the Effect of Average School Length and School Length Expectancy on The Human Development Index in Lebak Regency, Banten Province, in 2011–2024 - Humaeroh, Siti; Agustin, Elsa (MID Publisher International, 2024)
This study aims to analyze the influence of the average length of school and the expectation of length of school on the Human Development Index (HDI) in Lebak Regency, Banten Province, for the period 2011–2024. HDI is an important indicator in measuring the quality of human development which consists of three main dimensions: health, education, and economy. This study specifically focuses on the education dimension, with average length of school and expectation of length of school as independent variables. The research method uses a quantitative approach with secondary data obtained from the Central Statistics Agency of Lebak Regency, Banten Province, and Indonesia. Data analysis was carried out through descriptive statistics, classical assumption tests, and multiple linear regression. The results showed that partially the average length of school (RLS) had a significant effect on HDI with a significance value of 0.000 and t-count of 10.088. In contrast, the long-term expectation of school (HLS) had a partially insignificant effect with a significance value of 0.058 and a t-count of 2.112. However, simultaneously, these two variables had a significant effect on HDI with a significance value of 0.000 and an F-count of 211.902. The value of the determination coefficient (R²) of 0.975 shows that the education dimension contributes 97.5% to the increase in HDI in Lebak Regency. These findings confirm that education has a strategic role in sustainable human development.